(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
Age estimation from tooth has been a subject of research since 1950. This article traces the history of developments and critical components of the methods (both morphological and bio chemical) to calculate age at death for forensic purpose.